Transformasi Sosial Ekonomi Remaja Kampung Maibo Melalui Pelatihan Kerajinan Tangan dan Wirausaha Kreatif Berbasis Eco-Friendly - Rokhimah Rokhimah; Dwi Iin Kahinah; Ilham Nur Afandi; Institusi Agama Negeri Islam Sorong (Jurnal Pengabdian Masyarakat, 2025)
Rapid globalization and modernization have led to a decline in youth interest in local wisdom, including traditional skills such as handicrafts. Maibo Village in Sorong Regency, Southwest Papua, is a relocation area with a majority Kokoda population, which faces challenges in empowering youth economically. The objective of this community service activity is to empower youth in Maibo Village through eco-friendly handicraft and creative entrepreneurship training, such as utilizing scrap fabric and other recycled materials to create economically valuable and environmentally friendly products. The method used is Participatory Action Research (PAR), with an approach of technical training, business mentoring, and the formation of youth entrepreneurial groups. Data was obtained through field observations, participatory surveys, and interviews with community leaders. The focus of this activity is on the youth community in Maibo Village, who lack productive skills and access to training. The results of the activity show an increase in youth knowledge, creativity, and skills in processing environmentally friendly materials into marketable products. In addition, this activity raises awareness of the importance of sustainable entrepreneurship and local economic potential. This program is expected to become a model for youth empowerment that encourages economic independence and can be replicated in other areas with similar characteristics.